Functional and structural changes of the urinary bladder following spinal cord injury; treatment with alpha lipoic acid - VELİOĞLU ÖĞÜNÇ, AYLİZ; YEGEN, BERRAK; AKAKIN, DİLEK; ÖZSAVCI, DERYA; ŞENER, GÖKSEL; ÖZDEMİR KUMRAL, ZARİFE NİGAR (WILEY, 2017)
BACKGROUND & AIMAlpha lipoic acid (LA) was shown to exert neuroprotection in trauma-induced spinal cord injury (SCI), which is frequently associated with urinary bladder complaints in patients with SCI. Accordingly, the protective effects of LA on biochemical and histological changes in bladder as well as functional studies were assessed. METHODSWistar albino rats were divided as control, SCI, and LA (50mg/kg/day, ip) treated SCI groups (SCI+LA). The standard weight-drop (100g/cm force at T10) method was used to induce a moderately severe SCI. One week after the injury, neurological examination was performed and the rats were decapitated. Bladder samples were taken for histological examination, functional (isolated tissue bath) studies, and for the measurement of biochemical parameters (malondialdehyde, MDA; gluthathione, GSH; nerve growth factor, NGF; caspase-3, luminol and lucigenin chemiluminescences). RESULTSSCI caused a significant (P<0.001) increase in the detrusor muscle thickness. It increased the contractility responses to carbachol and relaxation responses to papaverine (P<0.05-0.001). There were also significant alterations in MDA, caspase-3, luminol, and lucigenin chemiluminescences with concomitant decreases in NGF and GSH (P<0.05). LA treatment reversed histological and functional (contraction and relaxation responses) changes induced by SCI (P<0.05-0.001), but no significant recovery was observed in the impaired neurological functions. CONCLUSIONThese results indicate that LA have a beneficial effect in improving the bladder tonus via its antioxidant and anti-inflammatory actions following SCI.
Keywords: bladder; carbachol; caspase 3; contractility; lipoic acid; NGF; NSE; papaverinee; relaxation; S100; spinal cord injury; trauma; OXIDATIVE STRESS; DYSFUNCTION; UROTHELIUM; RAT